Improving dementia care: a multi-sensory stimulation approach - Cruz, J. (2020)
This pilot-study examined the effects of a Multisensory Stimulation (MSS) programme on the interaction of residents with dementia. Six residents with moderate/severe dementia from an old people’s home were recruited. Six staff members received 8 training sessions and assistance to implement MSS in dementia care. Observational data on residents’ behaviour during morning care was collected pre- and post-intervention. Results suggest improvements of caregiver-direct gaze, laugh, verbal communication and task involvement, and a reduction of closed-eyes. The introduction of MMS during care routines may improve residents’ involvement and facilitate communication, potentially improving their well-being.